(untitled) (SAARC Journal of Agriculture, 2016)
The experiment was carried out at the District Seed Farm, Adisaptagram, Hooghly (West Bengal), India during two consecutive winter seasons of 2011-12 and 2012-13 to find out optimum N dose of potato cultivars for getting higher yield as well as to identity efficient potato cultivars regarding N use. Average yield of potato cultivars increased significantly with increase in N supply up to 225 kg N ha-1, then tended to decrease slightly as nitrogen levels increased further. Tuber yield of cultivars Kufri Shailja and Kufri Jyoti was increased significantly with increase in nitrogen level up to 225 kg N ha-1 and further addition of N decreased yield. Yield of Kufri Himalini was increased with increase in N level up to 300 kg N ha-1 but the yield increment from 225 kg N ha-1 to 300 kg N ha-1 was not significant. Application of less N decreased average potato tuber yield by 5.3, 18.7 and 65.1% with 150, 75 and 0 kg N ha-1 respectively, compared to 225 kg N ha-1. Nitrogen use efficiency (NUE) decreased towards higher N levels for all cultivars. NUE of Kufri Himalini was higher at all N levels. The results revealed that irrespective of cultivar 225 kg N ha-1 was the optimum for getting higher tuber yield of potato and cultivar Kufri Himalini was the most efficient in case of N use. SAARC J. Agri., 13(2): 141-150 (2015)